Secondary thrombotic microangiopathy with severely reduced ADAMTS13 activity in a patient with Capnocytophaga canimorsus sepsis: a case report. Issue 10 (17th September 2018) - Smeets, Nori J.L.; Fijnheer, Rob; Sebastian, Silvie; De Mast, Quirijn
Abstract : BACKGROUND: The Gram‐negative bacillus Capnocytophaga canimorsus may cause a severe illness resembling thrombotic thrombocytopenic purpura (TTP). The pathogenesis and optimal therapy of this secondary thrombotic microangiopathy (TMA) remain uncertain. CASE REPORT: A 63‐year‐old Caucasian man was admitted with suspicion for TTP, but blood cultures grew C. canimorsus . Initial investigations revealed severe thrombocytopenia, a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) activity level of less than 1%, and strongly elevated D‐dimer and lactate dehydrogenase levels. He made a full recovery with antibiotics and plasma infusion for 3 days. Plasmapheresis was not performed. Retrospective determination of serial ADAMTS13 activity levels revealed that ADAMTS13 activity had already increased to 25% at the start of plasma infusion. CONCLUSION: This case highlights that a C. canimorsus sepsis may cause a secondary TMA with a severe ADAMTS13 deficiency. It also illustrates that the adjunctive role of plasma exchange or plasma infusion is doubtful as ADAMTS13 activity levels increased with antibiotics alone.